Implementasi Model Problem-Based Learning untuk Meningkatkan Kemampuan Baca Tulis Al-Qur'an pada Siswa Madrasah Ibtidaiyah Negeri - Lisi Hartini; Sukarno Sukarno (Jurnal Indonesia Kajian Pendidikan Islam, 2025)
Background: Learning to read and write the Qur’an is a fundamental skill for students in Madrasah Ibtidaiyah. Traditional teaching methods often result in limited student engagement and lower learning outcomes. Implementing an active learning model, such as Problem-Based Learning (PBL), is expected to improve students’ Qur’an reading skills. Objective: This study aims to determine the improvement in students’ ability to read the Qur’an after the application of the PBL model. Method: The research was conducted using Classroom Action Research (CAR) in two cycles. Each cycle consisted of one meeting, which included action planning, implementation of the PBL model, observation, and reflection. Data were collected through observations, interviews, and documentation. Student learning outcomes were analyzed descriptively by comparing results from Cycle 1 and Cycle 2. Results: The findings indicate an improvement in students’ Qur’an reading skills in Class 2B at MIN 2 Bengkulu Selatan. Learning outcomes increased by 5%, from 62% in Cycle 1 to 67% in Cycle 2, within four days of implementing the PBL model. Conclusion: The PBL model effectively enhances students’ Qur’an reading skills by fostering active participation and problem-solving abilities. Contribution: This study guides teachers on implementing PBL to improve Qur’an reading learning outcomes, promoting active learning and student engagement in Madrasah Ibtidaiyah.